A Comprehensive Review of Neurologic Manifestations of COVID-19 and Management of Pre-existing Neurologic Disorders in Children. (March 2021) - Kim, Yunsung; Walser, Sarah A.; Asghar, Sheila J.; Jain, Rohit; Mainali, Gayatra; Kumar, Ashutosh
Since the first reports of SARS-CoV-2 infection from China, multiple studies have been published regarding the epidemiologic aspects of COVID-19 including clinical manifestations and outcomes. The majority of these studies have focused on respiratory complications. However, recent findings have highlighted the systemic effects of the virus, including its potential impact on the nervous system. Similar to SARS-CoV-1, cellular entry of SARS-CoV-2 depends on the expression of ACE2, a receptor that is abundantly expressed in the nervous system. Neurologic manifestations in adults include cerebrovascular insults, encephalitis or encephalopathy, and neuromuscular disorders. However, the presence of these neurologic findings in the pediatric population is unclear. In this review, the potential neurotropism of SARS-CoV-2, known neurologic manifestations of COVID-19 in children, and management of preexisting pediatric neurologic conditions during the COVID-19 pandemic are discussed.